BLINDED BY METASTASIS: A RARE CASE OF RENAL CELL CARCINOMA IN THE PITUITARY - Ismail, Ilham; Mahadi, Mahrunissa; Abas, Syarifah Syahirah Syed; Low, Chee Koon; Devaraja, Vanusha; Yong, Fei Bing; Wahab, Norasyikin A.; Mustafa, Norlaila (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Renal cell carcinoma (RCC) is the most common primary kidney tumor, accounting for 1–3% of adult malignancies. Metastasis of RCC to the pituitary gland is extremely rare, with only a few reported cases. The time interval from primary tumor diagnosis to pituitary metastasis ranges from 3 months to 27 years, with a median interval of 1 year. Surgical resection is the treatment of choice in cases where vision deteriorates due to optic nerve compression. Adjuvant therapies may also be used, including radiotherapy, chemotherapy, immunotherapy, or targeted therapy. Here, we report a case of RCC metastasis to the pituitary presenting with impaired vision. CASE A 62-year-old healthy male presented with progressive blurring of vision in both eyes, where the left eye was completely blind, and the right eye had tunnel vision. Constitutional symptoms occurred four months after undergoing right nephrectomy for RCC stage III. Magnetic resonance imaging revealed an enlarged sella with a solid lesion extending into the suprasellar region, compressing the bilateral optic chiasm and abutting both anterior cerebral arteries. He underwent transsphenoidal surgery, but the procedure was incomplete due to significant bleeding from the vascularized tumor. Two months later, a second decompression surgery was performed to preserve both the optic nerve and chiasm. Postoperatively, he developed panhypopituitarism and required hormone replacement therapy with thyroxine and hydrocortisone. Histopathology examination confirmed metastasis of clear cell renal carcinoma. Hence, radiotherapy and the tyrosine kinase inhibitor (TKI) Pazopanib were used as adjuvant therapies. Following treatment, the patient’s vision remained stable, with neither improvement nor further deterioration. CONCLUSION This case underscores the rarity of pituitary metastases from renal cell carcinoma and emphasizes the need for clinicians to consider this complication among patients with unexplained neurological symptoms. A multidisciplinary treatment approach with radiotherapy and TKI has potential benefits in challenging cases with incomplete surgical resection.